Mepivacaine versus Bupivacaine Spinal Anesthesia for Early Postoperative Ambulation: A Randomized Controlled Trial. (October 2020) - Schwenk, Eric S.; Kasper, Vincent P.; Smoker, Jordan D.; Mendelson, Andrew M.; Austin, Matthew S.; Brown, Scot A.; Hozack, William J.; Cohen, Alexa J.; Li, Jonathan J.; Wahal, Christopher S.; Baratta, Jaime L.; Torjman, Marc C.; et al.
Abstract : Background: Early ambulation after total hip arthroplasty predicts early discharge. Spinal anesthesia is preferred by many practices but can delay ambulation, especially with bupivacaine. Mepivacaine, an intermediate-acting local anesthetic, could enable earlier ambulation than bupivacaine. This study was designed to test the hypothesis that patients who received mepivacaine would ambulate earlier than those who received hyperbaric or isobaric bupivacaine for primary total hip arthroplasty. Methods: This randomized controlled trial included American Society of Anesthesiologists Physical Status I to III patients undergoing primary total hip arthroplasty. The patients were randomized 1:1:1 to 52.5 mg of mepivacaine, 11.25 mg of hyperbaric bupivacaine, or 12.5 mg of isobaric bupivacaine for spinal anesthesia. The primary outcome was ambulation between 3 and 3.5 h. Secondary outcomes included return of motor and sensory function, postoperative pain, opioid consumption, transient neurologic symptoms, urinary retention, intraoperative hypotension, intraoperative muscle tension, same-day discharge, length of stay, and 30-day readmissions. Results: Of 154 patients, 50 received mepivacaine, 53 received hyperbaric bupivacaine, and 51 received isobaric bupivacaine. Patient characteristics were similar among groups. For ambulation at 3 to 3.5 h, 35 of 50 (70.0%) of patients met this endpoint in the mepivacaine group, followed by 20 of 53 (37.7%) in the hyperbaric bupivacaine group, and 9 of 51 (17.6%) in the isobaric bupivacaine group ( P < 0.001). Return of motor function occurred earlier with mepivacaine. Pain and opioid consumption were higher for mepivacaine patients in the early postoperative period only. For ambulatory status, 23 of 50 (46.0%) of mepivacaine, 13 of 53 (24.5%) of hyperbaric bupivacaine, and 11 of 51 (21.5%) of isobaric bupivacaine patients had same-day discharge ( P = 0.014). Length of stay was shortest in mepivacaine patients. There were no differences in transient neurologic symptoms, urinary retention, hypotension, muscle tension, or dizziness. Conclusions: Mepivacaine patients ambulated earlier and were more likely to be discharged the same day than both hyperbaric bupivacaine and isobaric bupivacaine patients. Mepivacaine could be beneficial for outpatient total hip arthroplasty candidates if spinal is the preferred anesthesia type. Abstract : In this randomized, three-arm study involving 154 patients, more individuals in the mepivacaine spinal group ambulated 3 to 3.5 h after injection than did individuals in either the isobaric or hyperbaric bupivacaine group. Likewise, more patients in the mepivacaine group achieved same-day discharge than patients in the other experimental groups.